Pengaruh Pengumuman Right Issue Terhadap Tingkat Keuntungan Pada Saham Perbankan Dan Lembaga Keuangan Di Bursa Efek Indonesia - ', Rusli (Jurnal Ekonomi, 2010)
This main objective of this study is to examine the empirically divestiture and alliance transactionsannouncement shown in the abnormal returns of company who doing that transactions. Particularly,this study test the implication of the divestiture and alliance transactions characteristic andcompany`s characteristic who doing that transactions reflected by return and abnormal returnsduring event windows. This study uses bank and financial company who listed in Bursa EfekIndonesia (BEI) during period 1999-2006.Hypothesis testing uses T-Test Independent to known empirically divestiture and alliance transactionsannouncement shown in the abnormal returns of company who doing that transactions.